(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2016)
In recent years the number of scholarly publications devoted to Kant’s theory of biology has rapidly growing, with particular attention being given to Kant’s thoughts about the concepts of teleology, function, organism, and their respective roles in scientific practice. Moving from these recent studies, and distancing itself from their mostly evolutionary background, the main aim of the present paper is to suggest an original "cognitive turn" in the interpretation of Kant’s theory of biology. More specifically, the Authors will trace a connection between some Kantian theses about the “peculiar” or special nature of the human mind (intellectus ectypus), advanced in the Critique of the Power of Judgement (§ 76, 77), and some specific epistemological issues pertaining to the research practice of contemporary molecular biology.